Faktor-Faktor yang Mempengaruhi Partisipasi Pekerja Informal dalam Program BPJS Ketenagakerjaan di Kota Denpasar - Aziz, Mu'adz Abdul; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 12 (2022): Vol.11.12. DESEMBER 2022[4234-4463]DO - 10.24843/EEP.2022.v11.i12.p13, 2022)
The research objectives are: 1) to analyze the simultaneous influence of income, socialization, and attitudes on the opportunity to participate informal workers in the BPJS Ketenagakerjaan program in Denpasar City; 2) to analyze the partial influence of income, socialization, and attitudes on the opportunity to participate informal workers in the BPJS Ketenagakerjaan program in Denpasar City. This research uses primary data, data collection is done through observation and interviews with a sample of 100 respondents located in Denpasar City. The analysis technique used is factor analysis, model fit test and logistic regression. The results of this study are: 1) simultaneously income, socialization and attitudes affect the opportunity to participate informal workers in the BPJS Ketenagakerjaan program in Denpasar City; 2) Partially, income has no effect on the opportunity to participate informal workers in the BPJS Ketenagakerjaan program, while socialization and attitudes have a positive effect on the opportunity to participate informal workers in the BPJS Ketenagakerjaan program in Denpasar City.